Distributed robust output consensus for linear multi‐agent systems with input time‐varying delays and parameter uncertainties. Issue 2 (1st January 2019) - Fiengo, Giovanni; Lui, Dario Giuseppe; Petrillo, Alberto; Santini, Stefania
Abstract : This study addresses the leader‐tracking problem for linear multi‐agent systems in the presence of both parameter model uncertainties and time‐varying communication delays. To solve the robust output consensus problem, a delayed distributed proportional–integral–derivative control is proposed and the overall closed‐loop stability is proven by exploiting the Lyapunov–Krasovskii theory. Delay‐dependent robust stability conditions are given via linear matrix inequalities which allow the proper tuning of robust control gains. The effectiveness of the theoretical derivation is confirmed through a numerical analysis in the practical application domain of cooperative driving for connected vehicles.